Chronic tophaceous gout in an adult - Ana Maria Ortiz Olivares; Odisa Mildres Cortés Ross; Deisy de los Milagros Torres Motas (Centro Provincial de Información de Ciencias Médicas, 2019)
The case report of a 57 year-old  mestizo patient, is presented with a history of rheumatoid arthritis and gout who visited the specialized Dermatology department of "Celia Sánchez Manduley" Teaching Clinical-Surgical Hospital in Manzanillo, Granma province, for presenting disseminated painful nodular lesions. Complementary studies and skin biopsy were carried out which results allowed to diagnose a chronic . The patient was under drugs treatment with prednisona, colchicina and metrotexate, but after discussing the case with the specialists in internal medicine and rheumatology it was decided to sustitute colchicina by alopurinol.